Mathematics of Multi-Level Complex Systems - Volchenkov, D. (Discontinuity, Nonlinearity, and Complexity, 2026)
special issue of the Journal “Discontinuity, Nonlinearity, and Complexity” contains the proceedings of the joint workshop “Mathematics of Complex Systems” that took place at the Center for Interdisciplinary Research of the University of Bielefeld on the 7-9 October, 2013 supported by the Work program of FP7: FET Proactive Intiative of the European Comission: “Dynamics of Multi-Level Complex Systems (DyM-CS)”.